Charateristic Changes of Shark and Stingray Surimi as Affected By Compositioning and Chill Storage of the Mince Fish - Joko Santoso; Ade Wiguna Nur Yasin; Santoso . (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2008)
This experiment was carried out to study the effects of leaching, compositioning, and chill storage of mince fish on the characteristic changes of surimi from shark and stingray as much as 88% and 100%, respectively; with the salt soluble protein contents were 13.52% and 13.24%, repectively. Mixture of mince shark and stingray in proportion of 25% : 75% (A1B A2) gave the highest value of gel strength being 209.29 g.cm in comparison with others composition. During chill storage , deterioration process still occurred as indicated by increasing value of acidity and content of base volatile compounds i.e. total volatile base nitrogen (TVBN) and tri-methyl amine (TMA); and also decreasing contents of urea and salt soluble protein. Deterioration process of mince fish also affected the physical characteristic of surimi i.e decreasing values of gel strength, water holding capacity (WHC), and colour (whiteness). Key word : chill storage, compositioning, mince-fish, shark, stingray, surimi